Influence of Irradiation on Leukodepleted Small Unit Red Blood Cell (RBC) Bags for Infant Transfusion in Additive Solution SAG-M - Hauck-Dlimi, Barbara; Schiffer, Katharina; Eckstein, Reinhold; Strobel, Joachim; Zimmermann, Robert (Clinical Laboratory, 2016)
BACKGROUND: To reduce transfusion-associated graft-versus-host disease irradiation of blood products is widely accepted. There is little data about the effect of gamma-irradiation on leukoreduced RBCs stored in SAG-M that are subdivided for use in transfusion to preterm infants and small children. METHODS: We studied 30 leukoreduced SAG-M preserved RBC bags. All RBCs were leukoreduced on the collection day. The 30 units were divided into two groups. Every unit was divided into three bags. One of these bags served as nonirradiated control (group 1A, group 2A), the other two were gamma-irradiated at different times. In vitro evaluation of irradiated and nonirradiated units was performed on the days +3, +7, +14, +21, and +28 from the day of collection. RESULTS: Gamma irradiation induced a higher increase of extracellular hemoglobin, LDH, and potassium than non-irradiated storage over the time. No irradiated or non-irradiated unit showed a hemolysis rate over the recommended limit of 0.8% over the 28 day period. CONCLUSIONS: Our findings show that subdivision of RBCs does not have an appreciable influence on the storage of leukoreduced, irradiated RBCs in AS SAG-M. Our "worst case scenario" was irradiation on day +3 after donation and subsequent storage until day +28. Especially for infant use, it is important to have the possibility to irradiate even late after donation, because this procedure offers the possibility to use one RBC bag over a longer period of time and to reduce the donor exposure for infants. Therefore, subdivided leukoreduced RBCs can be safely irradiated until day +14 and subsequently stored until day +28 after donation.
EVALuna2:32775